Quercetin Derivatives in Combating Spinal Cord Injury: A Mechanistic and Systematic Review - Echeverria-Morgado, J (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Spinal cord injury (SCI) possesses a complicated etiology. There is no FDA-approved treatment for SCI, and the majority of current interventions focus on reducing symptoms. During SCI, inflammation, oxidative stress, apoptosis, and autophagy are behind the secondary phase of SCI and cause serious consequences. It urges the need for providing multi-targeting agents, that possess lower side effects and higher efficacy. The plant secondary metabolites are multi-targeting agents and seem to provide new roads in combating diseases. Flavonoids are phytochemicals of continual interest to scientists in combating neurodegenerative diseases (NDDs). Flavonoids are being studied for their biological and pharmacological effects, particularly as antioxidants, anti-inflammatory agents, anti-apoptotic, and autophagy regulators. Quercetin is one of the most well-known flavonols known for its preventative and therapeutic properties. It is a naturally occurring bioactive flavonoid that has recently received a lot of attention for its beneficial effects on NDDs. Several preclinical evidence demonstrated its neuroprotective effects. In this systematic review, we aimed at providing the biological activities of quercetin and related derivatives against SCI. Detailed neuroprotective mechanisms of quercetin derivatives are also highlighted in combating SCI. © 2022 by the authors.
Keywords: quercetin; spinal cord injury; inflammation; apoptosis; oxidative stress; pharmacology